Answer:
f(x)-g(x)=x^2+9x+2
Step-by-step explanation:
f(x)-g(x)=(3x^2+6x-1)-(2x^2-3x-3)
=3x^2+6x-1-2x^2+3x+3
=(3x^2-2x^2)+(6x+3x)+(-1+3)
=x^2+9x+2
One pair of vertical angles measures 90 degrees each, and the other pair of vertical angles measures 90 degrees each as well.
When two lines intersect, they form four angles. The angles that are opposite each other, called vertical angles, are equal. The sum of the measures of the vertical angles and the adjacent angles is 180° because they form a straight line.
Solving for x we get:
2x + 180 - x = 270
x = 90
Therefore, one pair of vertical angles measures 90 degrees each, and the other pair of vertical angles measures 90 degrees each as well.
Read more on angles here brainly.com/question/25770607
#SPJ2
Answer:
120
Step-by-step explanation:
Because we know that the line opposite of the right angle is flat, we know that 60 plus x must equal 180. Rewriting this gives us 180 - 60 = x.
Now, we can just solve for x.
x = 120.
Answer:
Step-by-step explanation:
∠A=∠B
4X+7=5X-3
X=7+3=10
5*10-3=50-3=47